Is three-dimensional ultrasonography a valuable diagnostic tool for patients with ovarian cancer? Systematic review and meta-analysis - Liu, Yuan; Zhang, Qingdong; Zhang, Fang; Liu, Meiyan; Zhang, Jun; Cao, Xiaoli; Yin, Weihong (Frontiers in Oncology, 2024)
This paper was to assess the diagnostic performance and clinical value of three-dimensional ultrasonography (3DUS), three-dimensional ultrasonography power Doppler (3DPD), and 3DUS combined with 3DPD in ovarian cancer (OC).The study was registered with PROSPERO (CRD 42023405765). PubMed and Web of Science were searched from inception to Jan 25, 2022, and reference lists of potentially eligible studies were also manually searched. Patient and study characteristics were extracted by two independent reviewers. Any discrepancies were addressed through discussion. The sensitivity, specificity, positive and negative likelihood ratio (PLR and NLR), and the area under the receiver operating characteristic curve (AUC) were pooled separately.We retrieved 2566 studies, of which 18 studies were finally enrolled, with 2548 cases. The pooled sensitivity, specificity, PLR, NLR, and AUC for 3DUS were 0.89 (95%CI: 0.85 to 0.93), 0.93 (95%CI: 0.88 to 0.96), 13.1 (95%CI: 7.3 to 23.4), 0.11 (95%CI: 0.08 to 0.16), and 0.90 (95%CI: 0.87 to 0.93), respectively. The pooled sensitivity, specificity, PLR, NLR, and AUC for 3DPD were 0.90 (95%CI: 0.80 to 0.95), 0.85 (95%CI: 0.71 to 0.92), 5.8 (95%CI: 3.0 to 11.2), 0.12 (95%CI: 0.06 to 0.24), and 删除了: We aimed 51 删除了: doppler 52 删除了: identified primary 53 删除了: Our search 54 删除了: fulfilled the inclusion criteria 55 3 0.94 (95%CI: 0.91 to 0.96), respectively. The pooled sensitivity, specificity, PLR, NLR,and AUC for 3DUS combined with 3DPD were 0.99 (95%CI: 0.73 to 1.00), 0.95 (95%CI: 0.85 to 0.99), 21.9 (95%CI: 6.1 to 78.9), 0.01 (95%CI: 0.00 to 0.37), and 0.99 (95%CI: 0.98 to 1.00), respectively.Conclusions: 3DUS, 3DPD, and 3DUS combined with 3DPD are promising diagnostic tools for OC, alongside elevated sensitivity and specificity. However, the combination of 3DUS and 3DPD techniques has higher diagnostic efficiency.